Motivational goal bracketing - Alexander K. Koch; Julia Nafziger (Institute for the Study of Labor (IZA), 2009)
It is a puzzle why people often evaluate consequences of choices separately (narrow bracketing) rather than jointly (broad bracketing). We study the hypothesis that a present-biased individual, who faces two tasks, may bracket his goals narrowly for motivational reasons. Goals motivate because they serve as reference points that make substandard performance psychologically painful. A broad goal allows high performance in one task to compensate for low performance in the other. This partially insures against the risk of falling short of ones' goal(s), but creates incentives to shirk in one of the tasks. Narrow goals have a stronger motivational force and thus can be optimal. In particular, if one task outcome becomes known before working on the second task, narrow bracketing is always optimal.
urn:nbn:de:101:1-20091015819
Keywords: A12; C70; D91; 330; Goals; multiple tasks; motivational bracketing; self-control; time inconsistency; psychology; Leistungsmotivation; Verhaltensökonomik; Anforderungsprofil; Risikopräferenz; Zeitkonsistenz; Arbeitspsychologie; Theorie